تأثير موقع تيك توك على التنشئة الاجتماعية لدى المراهقين - العيد بن حمده; خالد بن عمر (جامعة الوادي - University of Eloued, 2025)
"تأتي هذه الدراسة لتسلط الضوء على تأثير موقع تيك توك على التنشئة الاجتماعية لدى المراهقين، وعلى وجه الخصوص مراهقي ثانوية غربي بشير بحاسي خليفة، وقد تم معالجة إشكالية الدراسة من خلال طرح التساؤل التالي :ما هو تأثير موقع تيك توك على التنشئة الاجتماعية لدى مراهقي ثانوية غربي بشير بحاسي خليفة؟ وقد سعت هذه الدراسة إلى الكشف عن الأبعاد المختلفة التي يُحدث من خلالها موقع تيك توك تأثيره على المراهقين، سواء من حيث القيم والمعايير الاجتماعية، أو من خلال سلوكياتهم واتجاهاتهم الفكرية، كما تهدف الدراسة إلى التعرف على مدى تأثير استخدام موقع تيك توك لدى فئة المراهقين. أما عن الإجراءات المنهجية المعتمدة، فتندرج دراستنا ضمن الدراسات الوصفية، وقد تم الاعتماد على المنهج المسحي بوصفه الأنسب لطبيعة الموضوع. وتم اختيار تلاميذ الثانويات ليكونوا كمجتمع بحث، وتم تحديد 70 مفردة بطريقة العينة القصدية، حيث تم تحديد تلاميذ ثانوية غربي بشير بحاسي خليفة، باعتبارهم عينة ممثلة للمجتمع الكلي. واعتمدنا في دراستنا على أداة استمارة الاستبيان كأداة رئيسية لجمع المعطيات. تم تقسيم خطة البحث إلى ثلاث فصول أساسية، تناول الفصل الأول الإطار المفاهيمي للدراسة، بينما خصص الفصل الثاني للإطار النظري المتعلق بموقع تيك توك والتنشئة الاجتماعية. أما الفصل الثالث فقد عالج الإطار التطبيقي وعرض نتائج الدراسة ومناقشتها. وقد توصلت الدراسة إلى عدة نتائج هامة من أبرزها: . أن معظم المراهقين المدروسين يستخدمون موقع تيك توك منذ أكثر من سنتين، ما يشير إلى علاقة طويلة المدى به. • يتم استخدام موقع تيك توك غالبًا داخل المنزل، وفي الغالب بشكل فردي، ويقضي أغلبهم أكثر من ساعة يوميًا. • الدافع الأساسي لمعظم أفراد العينة المدروسة هو التسلية وتمضية الوقت، تليه دوافع مثل الهروب من الضغوط. . الغالبية ممن تمت عليهم الدراسة يستخدمون أسماء أو صور مستعارة. • نسبة معتبرة من المراهقين أقروا بتأثير سلبي على مستواهم الدراسي بسبب استخدام موقع تيك توك. . هناك حالات من العينة اكتسبت قيم وثقافات جديدة من مجتمعات أخرى بفضل تأثير محتويات الموقع. . عدد من المستخدمين صرحوا بأن وقتهم مع العائلة قد تقلّص منذ استخدامهم للمنصة." "Study Summary: This study aims to shed light on the impact of TikTok on the socialization of adolescents, with a specific focus on students at Gharbi Bachir High School in Hassi Khalifa. The research problem is addressed through the following central question: What is the impact of TikTok on the socialization of adolescents at Gharbi Bachir High School in Hassi Khalifa? The study seeks to explore the various dimensions through which TikTok influences adolescents, including social values and norms, as well as their behaviors and intellectual orientations. It also aims to assess the extent of TikTok's influence on the adolescent demographic. Methodologically, this research falls under the category of descriptive studies and adopts the survey method, deemed most appropriate for the nature of the subject. High school students were selected as the research population, and a purposive sample of 70 students from Gharbi Bachir High School in Hassi Khalifa was chosen as a representative group. The main data collection tool employed was a structured questionnaire. The research structure consists of three main chapters: the first chapter presents the conceptual framework of the study; the second focuses on the theoretical framework related to Tiktok and socialization; and the third chapter addresses the applied aspect, presenting and discussing the findings. The study yielded several key results, most notably: The majority of adolescents studied have been using TikTok for more than two years, indicating a long-term engagement with the platform. TikTok is primarily used at home and usually individually, with most participants spending over an hour daily on the platform. The primary motivation for use among the sample is entertainment and passing time, followed by reasons such as escaping pressure. A large number of participants use pseudonyms or avatars instead of real names and photos. A significant proportion of adolescents acknowledged a negative impact on their academic performance due to TikTok use. Some respondents reported acquiring new values and cultural elements from other societies through the platform's content. Several users noted a reduction in time spent with family since they began using the app. "
مذكرة ماستر قسم اعلام واتصال تخصص سمعي بصري
Keywords: المراهقون; تيك توك التنشئة الاجتماعية; TikTok; socialization; adolescents.